Assessment and student motivations through the lens of agency theory - JONGJAROENKAMOL, Prasart (Institutional Knowledge at Singapore Management University, 2020)
Assessment is used to evaluate student learning and to motivate students to learn. Instructors generally have the option of using individual assessment, team assessment, or a combination of both. Using a principal-agent model, this study analytically examines how individual assessment and team assessment affect students' incentives to learn when their abilities vary. Relative to individual assessment, team assessment imposes more uncertainties on students, but it also encourages strong students to cooperate with weak students to help them learn. Depending on the strengths of these two forces, it can be optimal for the instructor to use individual assessment only or a combination of both individual and team assessment. In addition, this study shows that as the weight applied to the team assessment component increases, students' motivation to learn can increase or decrease, suggesting a non-monotonic relationship. Finally, this study suggests some factors that affect the optimal weight assigned to the team assessment component and the individual assessment component.